A Case Study on the Implementation of Curriculum Management Implementation of the Sekolah Penggerak Program at the Junior High School Level - Elly Nurdjanah; Yuli Eka Purwanti; Karwanto Karwanto; Ainur Rifqi Ima; Widiyanah Widiyanah (Universitas Teuku Umar, 2025)
The School Activator Program (PSP) is an initiative of the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) to encourage educational transformation through improving the quality of curriculum management. This study was conducted to examine the implementation of PSP curriculum management at UPT SMP Negeri 3 Gresik. This research uses a qualitative approach with a case study design to explore the implementation of curriculum management in depth. Data collection was carried out using three main techniques: (1) semi-structured interviews with teachers and educational staff, (2) direct observation of the learning process, and (3) document review in the form of program notes for the 2022-2024 period. The results of the study show that there is a broad curriculum management system that includes: (1) Curriculum planning based on school characteristics and student profiles; (2) Curriculum implementation, namely intracurricular activities such as the application of a differentiated learning approach, cocurricular (Pancasila Student Profile Strengthening Project), and extracurricular activities; (3) Curriculum evaluation and continuous professional development by disseminating information to six educational institutions. UPT SMP Negeri 3 Gresik has succeeded in becoming a model in implementing PSP (4) The main challenge faced is the adaptation of teachers to internal changes and changes in the affected schools. Conclusion: The implementation of PSP curriculum management at SMP Negeri 3 Gresik has shown progress in innovative learning approaches, although it requires strengthening in terms of mentoring and infrastructure. These findings can be used as a reference for other schools in implementing PSP and as evaluation material for policy makers.